Has the Paycheck Protection Program Succeeded? - Glenn Hubbard; Michael R. Strain (Institute of Labor Economics (IZA), 2020)
Enacted March 27, 2020, the Paycheck Protection Program (PPP) was the most ambitious and creative fiscal policy response to the Pandemic Recession in the United States. PPP offers forgivable loans — essentially grants — to businesses with 500 or fewer employees that meet certain requirements. In this paper, we present evidence that PPP has substantially increased the employment, financial health, and survival of small businesses, using data from the Dun & Bradstreet Corporation. We use event studies and standard difference-in-difference models to estimate the effect of a small business applying for larger PPP loans and of a small business being eligible for PPP based on size. While our findings are informative, we believe it is too early to issue conclusive judgment on PPP's success. We offer lessons for the future from the PPP experience thus far.
Keywords: H20; H25; H32; J01; J08; J23; 330; Paycheck Protection Program; PPP; Pandemic Recession; CARES Act; COVID-19